The Forecasting of Financial Inclusion in East Java Through Islamic Microfinance Institution: an Autoregressive Integrated Moving Average Approach - Afandi, Muhammad Anif; A'yun, Indanazulfa Qurrota (Journal of Developing Economies, 2018)
Financial inclusion is an effort intended to eliminate price and non-price barriers toward public access to formal financial institutions. The aim of that is income equalization of the societies affecting increasing economic growth, poverty alleviation, and financial system stability. East Java is one of the provinces in Indonesia with the most number of Islamic Rural Banks (BPRS). This study wants to find out how the role of BPRS in realizing the acceleration of Islamic financial inclusion in East Java. Then, this research is conducted in the period January 2014 – May 2018 in which data sourced from the Islamic Banking Statistics (SPS), Financial Services Authority (FSA). An Autoregressive Integrated Moving Average (ARIMA) is applied as research method to predict the level of Islamic financial inclusion in East Java through BPRS by using three from four financial inclusion indicators released by Bank Indonesia in 2014 namely access with number of BPRS as its proxy, usage with amount of third party funds and amount of financing as its proxies, and quality with total assets and Non-Performing Financing (NPF) as its proxies. The results show that based on forecasting values until December 2020, the number of BPRS predicted will decrease with the last number as many as 27 banks, DPK will increase with the last number 1,680,558.79 million Rupiah, the amount of financing will increase with the last number as many as 1,822,810.80 million Rupiah, asset will increase with the last number 2,299,250.44 million Rupiah, and NPF will increase with the last number 12.48 percent. Keywords: Financial Inclusion, Islamic Rural Banks, ARIMA, East Java JEL Classification: N25, G21